(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of histological types and comman sites of oral cancer in patients presenting at Liaquat University Hospital Jamshoro/Hyderabad Sindh. Study Design: Descriptive Study. Place and Duration of Study: This study was conducted on patients presenting at Oral and Maxillofacial Surgery Department, Liaquat university hospital Jamshoro/ Hyderabad Sindh over a period of one year from January 2010 to December 2010. Materials and Methods: Patients of all age group and gender with biopsy proven oral cancer along with its Histopathological types were included in the study. Patients reported irradiated,metastatic,benign and inflammatory lesions were excluded from the study. Results: Total number of patients was 100. There were 53 Males and 47 Females. Age range was 3years to 85years. means age was 44.2 years. Most comman site was cheeck mucosa. Histopathological analysis showed 75% patients having well diffrentiated squamous cell carcinoma, 13% patients having moderately diffrenciated squamous cell carcinoma, 2% patients having poorly diffrenciated anaplastic carcinoma,7% patients having basel cell carcinoma.1% Patients having Melanoma, 1% patients having Mucoepidermoid Carcinoma and 1% patients having Rhabdomyosarcoma. Conclusion: This study gives a detailed account of the histopathological types of oral cancer along with their frequency and site. oral cancer occurred at a younger age with male prepondrance.